THE ANALYZING OF CRITICAL THINKING SKILLS ON STUDENTS OF HIGH SHOOLS GRADE X IN PLAJU AND SEBERANG ULU II DISTRICT - Elsa Rinela Putri; Saleh Hidayat; Azwar Anas Harfian (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2018)
Based on the teacher questionnaire statement in Plaju and Seberang Ulu II District, the teacher has measured critical thinking skills. The teacher interview results stated that students still did not master the critical thinking skills of Biology High School. The purpose of this study was to determine the percentage level of mastery of critical thinking skills of class X high school students in Plaju and Seberang Ulu II District. This research is quantitative descriptive research; the sample used is a public high school representing the District of Plaju and Seberang Ulu II District. The results of this study indicate that, on average, the results of the percentage analysis of the level of student’s critical thinking skills in class X high school in Plaju District is 49.46%, and Seberang Ulu II District is 56.52%. Both the percentage of indicators critical thinking skills in Plaju and Seberang Ulu II District is in the medium category.